2018
DOI: 10.1007/s12029-018-0150-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of ki67 Index with Recurrence in Gastrointestinal Stromal Tumors

Abstract: We did not find an association of the ki67 index with recurrence. The factors associated with recurrence were a high tumor size (> 10 cm) and male sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Seagles-Rojas et al conducted a study to investigate the effect of Ki-67 index on GIST recurrence with 43 patients in 2018. In this study, Ki-67 had no effect on recurrence, but male gender and tumor size had ef-fect on recurrence (16). Like this study we found that Ki-67 have no relation with recurrence.…”
Section: Discussionsupporting
confidence: 63%
“…Seagles-Rojas et al conducted a study to investigate the effect of Ki-67 index on GIST recurrence with 43 patients in 2018. In this study, Ki-67 had no effect on recurrence, but male gender and tumor size had ef-fect on recurrence (16). Like this study we found that Ki-67 have no relation with recurrence.…”
Section: Discussionsupporting
confidence: 63%
“…Only four GISTs were analyzed for mutations at the time of the diagnosis, and all were negative for KIT and PDGFRA mutations. At the time of diagnosis, six of the eight GISTs were estimated to have a high risk for malignant behavior (size over >5 cm, and >5 mitoses per 50 high‐power microscopic fields, or Ki67 >5%), whereas the risk was low in two patients suggesting benign prognosis (Li et al, ; von Mehren & Joensuu, ; Segales‐Rojas, Lino‐Silva, Aguilar‐Cruz, & Salcedo‐Hernández, ; Zhou et al, ). However, the two NF1 patients with the low‐risk primary tumors in the duodenal localization died of GIST within one year of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the negative rate was as high as 22.09% in non-gastric tumors, and the negative rate from gastric sources was 0.59%. A study has shown that different sources of stromal tumors have different biological characteristics (25), and that lesions derived from the stomach have a better prognosis (26). Another study showed that CD34 has a high negative rate in large lesions, with the highest negative rate (13.04%) in the >10 cm group and the lowest negative rate (0%) in the ≤2 cm group (9).…”
Section: Relevance Of the Layer Of Invasion To Ki67mentioning
confidence: 99%